2-Bromopalmitate attenuates bone cancer pain via reversing mitochondrial fusion and fission imbalance in spinal astrocytes. (August 2019) - Meng, Wei; Hao, Miao-Miao; Yu, Na; Li, Ming-Yue; Ding, Jie-Qiong; Wang, Bang-Hua; Zhu, Hai-Li; Xie, Min
Bone cancer pain is common in patients with advanced cancers as tumors metastasize to bone. Pathogenesis of bone cancer pain is complex and poorly understood which leads to inefficiency of clinical treatment. During pathological pain status, astrocytes are activated and release various inflammatory cytokines, which result in the development of peripheral and central sensitization. As energy factory, mitochondria undergo frequent fusion and fission and play essential role for astrocyte function. 2-bromopalmitate (2-BP) is an inhibitor of protein palmitoylation, and its function on bone cancer pain was unclear. In this article, we aimed to investigate the potential curative effects and mechanisms of 2-BP on bone cancer pain. Bone cancer pain rat model was established through intratibial inoculation of rat mammary gland carcinoma cells (MRMT-1) into the left tibia of Sprague–Dawley female rats. As a result, bone cancer pain rats exhibited bone destruction and sensitive nociceptive behavior. And increased leukocyte infiltration, activation of astrocytes, and imbalance of mitochondrial fission and fusion dynamics were observed in spinal cord of bone cancer pain rats. Intrathecal 2-BP administration significantly attenuated pain behavior of bone cancer pain rats. Meanwhile, 2-BP administration reduced spinal inflammation, reversed spinal mitochondrial fission and fusion dynamic imbalance, and further inhibited spinal mitochondrial apoptosis in bone cancer pain rats. In C6 cell level, 2-BP treatment decreased dynamin-related protein 1 expression and increased optic atrophy 1 expression in a dose-dependent manner and inhibited carbonyl cyanide 3-chlorophenylhydrazone (CCCP)-induced mitochondrial membrane potential change. These data illustrated that 2-BP attenuated bone cancer pain by reversing mitochondrial fusion and fission dynamic imbalance in spinal astrocytes.